Determination of the influence of hemp oil-based emulsion systems composition on the oxidation products content during storage - Kunitsia, Ekaterina; Popov, Mykola; Gontar, Tatiana; Stankevych, Serhii; Zabrodina, Inna; Stepankova, Galyna; Zolotukhina, Olena; Filenko, Olesia; Novozhylova, Tetiana; Nechyporenko, Dmytro (Eastern-European Journal of Enterprise Technologies, 2024)
The object of the study is the content of antioxidants and the induction period of accelerated oxidation under simulated conditions of the lipid component of the emulsion system. The way to solve the problem of developing compositions of oxidation-stable emulsion systems based on nutritionally valuable oils, in particular hemp oil, by adding natural physiologically active antioxidants is considered. The research is relevant in the context of finding effective storage methods and extending the shelf life of products using hemp oil. The feature of the work lies in determining the influence of the composition of emulsion systems based on hemp oil on chemical oxidation during storage. The content of stabilizers in the hemp oil emulsion system (lecithin – 0.8...1.0 %; xanthan gum – 0.0...0.1 %) is proposed, which is effective in the inhibition of oxidative spoilage. The content range of β-carotene (0.012 %) in model emulsion systems is outlined, the addition of which increases the induction period of accelerated lipid oxidation by 1.58...2.08 times. The peroxide value of the lipid component of the emulsion system during storage at different temperature conditions (0...15 °C) and during different storage periods (15...60 days) was studied. The results of the study confirm the significant influence of the composition of emulsion systems on the chemical oxidation of the lipid component, which is important for ensuring the quality and stability of food, pharmaceutical and cosmetic products. An applied aspect of the obtained scientific result is the possibility of modeling the composition of emulsion systems based on valuable hemp oil depending on the ratio of polyfunctional antioxidants of the oil component